Evaluation of resistance to Fusarium solani in cassava genotypes (Research, Society and Development, 2022)
The development of cassava varieties resistant to Fusarium solani is economically viable for producers. For this, it is necessary to identify sources of resistance so that genetic parameters can be estimated, thus increasing information for breeders. The Fusarium genus is one of the main causes of damage, causing major economic impacts on cassava crops worldwide. Therefore, the aims of this work was to identify the levels of resistance to F. solani in cassava genotypes from the IFMS Germplasm Bank. Inoculation in previously autoclaved soil was performed by adding a mixture of sand and cornmeal, where a spore suspension was placed and grown for 20 days. For the control, only the mixture of sand and cornmeal was added to the soil. The experiment was carried out in a greenhouse. The experimental design adopted was completely randomized, with 41 treatments (genotypes), with six replications. In this paper we obtained genotypes grouped as resistant, moderately resistant, moderately susceptible and susceptible. The highlight of this study was the importance of cassava in the world production chain and the impact that root pathogens can cause to this crop.